A global survey of HIV‐positive people's attitudes towards cure research. Issue 2 (11th May 2016) - Simmons, R; Kall, M; Collins, S; Cairns, G; Taylor, S; Nelson, M; Fidler, S; Porter, K; Fox, J; ,
Abstract : Objectives: Involvement of people living with HIV (PLHIV) in the design of HIV cure studies is important, given the potential risks to participants. We present results of an international survey of PLHIV to define these issues and inform cure research. Methods: PLHIV were recruited in June−November 2014 through HIV websites, advocacy forums, social media and 12 UK HIV clinics. The survey included questions concerning demographics, HIV disease history, the desirability of types of cure and the patient's willingness to accept potential toxicity and treatment interruption (TI). We examined factors associated with TI and willingness to accept substantial risks. Results: A total of 982 PLHIV completed the survey; 87% were male, 79% white and 81% men who have sex with men (MSM). Fifty‐one per cent were aged 25–44 years and 69% were UK residents. The median time since diagnosis was 7 years [interquartile range (IQR) 2–17 years]. Eighty‐eight per cent were receiving antiretrovirals (91% reported undetectable viral load). Health/wellbeing improvements (96%) and an inability to transmit HIV (90%) were more desirable cure characteristics than testing HIV‐negative (69%). Ninety‐five per cent were interested in participating in cure studies, and 59% were willing to accept substantial risks. PLHIV with a low CD4 count [201–350 cells/ μ L vs . ≥ 350 cells/ μ L; odds ratio (OR) 2.11; 95% confidence interval (CI) 1.11–4.00] were more likely to accept risks, whereas those with limited knowledge of HIV treatments vs . excellent/good knowledge and those aged ≥ 65 years vs . 45–64 years were less likely to accept risks [OR 0.58 (95% CI 0.37–0.90) and OR 0.18 (95% CI 0.07–0.45), respectively]. TI was acceptable for 62% of participants, with the main concerns being becoming unwell (82%), becoming infectious (76%) and HIV spreading through the body (76%). Conclusions: Cure research was highly acceptable to the PLHIV surveyed. Most individuals would accept risks, including TI, even in the absence of personal benefit. An optimal cure would improve health and minimize onward transmission risk.